2022
DOI: 10.1055/s-0042-1744444
|View full text |Cite
|
Sign up to set email alerts
|

The Pathway of Female Couples in a Fertility Clinic

Abstract: Objective The present study aims to describe the main characteristics of female couples resorting to a fertility clinic, to understand whether these patients have clear previous plans concerning procreation and how they end up completing their family planning, and to briefly describe the main outcomes of the recepción de ovocitos de pareja (ROPA, in the Spanish acronym: in English, reception of partner's oocytes) method. Methods This is a descriptive retrospective study of the pathway and outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 19 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…They also found that passive patients in one-way reproductive techniques were 2 years older than active patients, but no differences were found within ROPA patients. 23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that passive patients in one-way reproductive techniques were 2 years older than active patients, but no differences were found within ROPA patients. 23 …”
Section: Resultsmentioning
confidence: 99%
“…Most of the women choose this method for this purpose, but others have a medical indication because one may choose the patient with the best ovarian and uterine prognosis for donor and recipient, respectively. 23 As for any type of ART, ROPA has many ethical issues far from being universally accepted. These dilemmas are mainly related to the risks of a nonessential procedure and the well-being of the offspring raised by a same-sex couple.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting example is the reception of oocytes from partner (ROPA) method, or lesbian shared IVF, in which both women share biological motherhood, one will be the gestational mother (the one giving birth) and the other will be the genetic mother (the one providing the oocytes). 133 In surrogacy, 3 people may be involved in motherhood: the carrier (which will be the birth mother), the oocyte provider and the intended mother (depending if it is with own or donated oocytes, these last two will be the same or different women, respectively). 134 In the majority of countries, legal motherhood is based upon the fact of birth.…”
Section: Ethical Issuesmentioning
confidence: 99%
“…This method allows both women of a same-sex couple to share biological motherhood. 29 One of them provides the oocytes (donor or genetic mother) and the other receives the resulting embryo (recipient or gestational mother). [30][31][32] Some define this method as a donation of oocytes (thus the name ROPA), others regard this technique as an embryo donation and others consider that it is not a donation at all, since it is within a couple, just as for conventional IVF for a heterosexual couple, in which the man provides the semen to his wife.…”
Section: Ropa -Lesbian Shared Ivfmentioning
confidence: 99%